2013
DOI: 10.5130/cjlg.v0i13/14.3726
|View full text |Cite
|
Sign up to set email alerts
|

Looking back, moving forward: Towards improving local governments' performance in Ghana

Abstract: This paper, based on a desk study, adopts a path-dependent perspective to explore how local government authorities in Ghana have attempted to institutionalise performance management at the organisational level. It questions the existing performance diagnostic framework that is used to assess local government authorities by arguing that any attempt to consolidate the prevailing ‘performance assessment regime’ ought to re-examine previous government initiatives that had in-built mechanisms for assessing local go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Evidence provided by Ayee (1996) and Crook (1994) are among the first attempts to assess the performance of newly created districts between 1988-92. Zakaria (2013) notes that no holistic assessment of local government performance existed before then. The key legislations establishing local governments in Ghana (Acts 462, 479, and 480) mandate monitoring and evaluation oversight to be exercised by the Regional Coordinating Councils (RCCs).…”
Section: Assessing Sub-national/local Government Performance Since 1988mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence provided by Ayee (1996) and Crook (1994) are among the first attempts to assess the performance of newly created districts between 1988-92. Zakaria (2013) notes that no holistic assessment of local government performance existed before then. The key legislations establishing local governments in Ghana (Acts 462, 479, and 480) mandate monitoring and evaluation oversight to be exercised by the Regional Coordinating Councils (RCCs).…”
Section: Assessing Sub-national/local Government Performance Since 1988mentioning
confidence: 99%
“…While a few studies are optimistic (see for example, Egbenya 2010), many others barely stop short of describing Ghana's decentralization experience as a failure, with sub-national government performance viewed as weak on several dimensions, including delivery of social services, such as education, health, and public housing (Frimpong Boamah 2018;Aziabah 2018;Yeboah-Assiamah 2016;Couttolenc 2012). There are also studies that review the methods or frameworks for analysing local government performance in Ghana (see for example Bawole and Ibrahim 2017;Zakaria 2013). 1 They demonstrate a lack of consensus on the 'how' of performance assessments in public sector governance structures, but this has not deterred efforts to make meaning of local government performance in Ghana (Zakaria 2013).…”
Section: Assessing Sub-national/local Government Performance Since 1988mentioning
confidence: 99%
“…There is also a growing consensus among public administration scholars that making organisations efficient is central not only to improving performance, but also to creating value for the general public (Van Dooren et al 2015;Henrich 2002). According to Zakaria (2013), many local governments in Ghana receive performance-oriented grantssuch as district development funds and other financial support from donor partnerswhich are typically tied to improved performance. Deploying performance management would help these local governments make the most of their grants, particularly given their enormous developmental responsibilities.…”
Section: Cjlg 2019mentioning
confidence: 99%
“…It is believed that local governments will be more efficient in the provision of poverty-reducing public goods and services than the central government (Manor 1999). Awortwi (2011) has even suggested that because local governments are theoretically accountable and It is now standard practice for local governments worldwide to be results-oriented, given their proximity to citizens and their direct responsibilities for service delivery (Perez-Lopez et al 2015;Ammons and Roenigk 2015;Zakaria 2013). It is therefore not surprising that local governments are using strategic planning to identify and prioritise community needs, and have turned to performance management as a means of pursuing their goals and avoiding the trap of merely complying with procedures in their work (Ammons and Roenigk 2015).…”
Section: Performance Management In Ghana's Local Governmentsmentioning
confidence: 99%
See 1 more Smart Citation